PENGARUH KENAIKAN TARIF PPN, INSENTIF PAJAK DAN DIGITALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM: Indonesia - Rahmawati, Pebi Amanda; Husni, Mohamad; Anggriawan, Muhammad Angga (Universitas Serang Raya, 2024)
This study aims to analyze the effect of VAT rate increases, tax incentives, and tax digitalization on MSME taxpayer compliance in Serang City. The research method used is the quantitative method. The population is 9,239 MSMEs registered at the Office of Cooperatives and Micro, Small, and Medium Enterprises (Dinkopukm) of Serang City, involving 99 respondents. The sampling technique used was the purposeful sampling method. The data analysis technique uses descriptive statistical analysis, data analysis tests, classical assumption tests, multiple regression analyses, and hypothesis testing using SPSS version 25.0 test aids. It can be concluded that the VAT Rate Increase and Tax Incentives have an influence on MSME Taxpayer Compliance in Serang City, while Tax Digitalization has no influence on MSME Taxpayer Compliance in Serang City. In addition, simultaneously the VAT Rate Increase, Tax Incentives and Tax Digitalization have a significant influence on MSME Taxpayer Compliance in Serang City